The Political Economy of Harmful Cultural Practices: Dowry and Son Preference as Economic Institutions - Shrestha, Hira Lal; Mallik, Aakriti Kumari; Tamang, Anita; Kafle, Namrata; Shrestha, Sumit; Khanal, Sumita (NPRC Journal of Multidisciplinary Research, 2025)
Background: Harmful Cultural Practices (HCPs) in Nepal, rooted in gender inequality, patriarchy, and superstition, pose significant challenges to public health, human rights, and social development. While research on this topic has grown, a comprehensive mapping of the intellectual structure and evolution of this literature is lacking. This study provides a systematic bibliometric review to visualize the research landscape, identify key themes, trends, and gaps. Methods: A systematic search was conducted in the Scopus and Web of Science core databases for publications from inception to December 2023. Keywords included "harmful cultural practices," "chhaupadi," "child marriage," "witchcraft accusation," "dowry," "Nepal," and related terms. Data were analyzed using the Bibliometric and VOSviewer for network visualization of co-authorship, keyword co-occurrence, and thematic clustering. Results: 148 relevant publications met the inclusion criteria. The analysis reveals a steady increase in publications since 2010, with a significant spike post-2017. Key findings include: (1) A dominant focus on the practice of Chhaupadi, often studied from a public health and menstrual hygiene perspective. (2) Strong thematic clusters around "Child Marriage" and its links to education and reproductive health, and "Gender-Based Violence" (GBV), including witch-hunting and dowry-related violence. (3) International scholars lead a significant portion of research, though Nepali institutional collaboration is growing. (4) The literature is fragmented, with limited cross-disciplinary integration between public health, legal, and sociological studies. Conclusion: This bibliometric analysis provides the first systematic map of research on HCPs in Nepal. It identifies a clear dominance of public health perspectives on specific practices, overshadowing critical socio-legal and political-economic analyses. Future research should prioritize community-led, intersectional, and policy-oriented studies that address the root causes of patriarchy and structural inequality, while exploring under-researched HCPs.